2007 4th IEEE International Symposium on Biomedical Imaging: From Nano to Macro 2007
DOI: 10.1109/isbi.2007.356993
|View full text |Cite
|
Sign up to set email alerts
|

A Fractal Multi-Dimensional Ultrasound Scatterer Distribution Model

Abstract: This paper presents a multi-dimensional point scatterer distribution model for the context of ultrasound image simulation. The model has a simple parameterisation, has low computational requirements and is flexible enough to model spatial organisation of scatterers ranging from highly clustered to nearly regular. The model extends an existing 1D model by mapping 1D scatterer positions to a Hilbert space-filling curve. The flexibility of the heuristic model is illustrated through experiments where common statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In order to quantitatively assess the parameter characterization and goodness of fit, Table 1 lists the mean and standard deviation of the estimated parameters and maximum likelihood values of the fitted distributions with different shape α and density ρ values. To obtain a more reasonable comparison for distributions having different numbers of free parameters, the “best-fitting” value was calculated using the likelihood value based on minimized Schwarz's Bayes information criterion (BIC) [ 33 ]: where L l is the value of the maximum log-likelihood, as well as n and m are the numbers of data samples and parameters in the model, respectively.. The likelihood values based on BIC of the fitted distributions by the HK, OKRR-based K, Rayleigh, and Rician are denoted as L HK , L K , L RA , and L RI , respectively.…”
Section: The Results and Discussionmentioning
confidence: 99%
“…In order to quantitatively assess the parameter characterization and goodness of fit, Table 1 lists the mean and standard deviation of the estimated parameters and maximum likelihood values of the fitted distributions with different shape α and density ρ values. To obtain a more reasonable comparison for distributions having different numbers of free parameters, the “best-fitting” value was calculated using the likelihood value based on minimized Schwarz's Bayes information criterion (BIC) [ 33 ]: where L l is the value of the maximum log-likelihood, as well as n and m are the numbers of data samples and parameters in the model, respectively.. The likelihood values based on BIC of the fitted distributions by the HK, OKRR-based K, Rayleigh, and Rician are denoted as L HK , L K , L RA , and L RI , respectively.…”
Section: The Results and Discussionmentioning
confidence: 99%
“…as a result of applying a Hilbert curve mapping to the output of the 1-d generalized Poisson point process, a set of m-d points is obtained whose spatial organization displays similar characteristics to that of the original 1-d points, as supported by empirical evidence of the preservation of local scatterer count statistics [7].…”
Section: M-d Generalized Poisson Modelmentioning
confidence: 92%
“…The lack of systematic positive interference effects in the multidimensional model used here is due to the isotropy of the Hilbert curve mapping. While the model preserves regularity, there is absolutely no guarantee that this regularity will be aligned with a particular direction although, as shown by some of the 2-d results in [7], this may occur. For positive interference effects to invariably occur, the scatterers must be placed quasi-periodically in the direction of wave propagation, at multiples of the transmitted wavelength.…”
Section: A First-order Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the other simulators, these micro-inhomogeneities are generally simulated by randomly placed scatterers (see [10] for example). More recently, Laporte et al [12] suggested to use the 1D marked regularity model of Cramblitt and Parker [7] and to extend it to higher dimensions. This model is based on the following scatterer function adapted to the 1D space domain:…”
Section: Tissue Modelingmentioning
confidence: 99%